Implications of property rights theory for the functioning of housing markets and housing policy - Żelazowski, Konrad (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The essential role of private ownership in optimal allocation of resources and efficiency of economic processes was underlined in classical economics by A. Smith or T. Malthus. However a complex analysis of the importance of property rights for economic development was undertaken by representatives of institutional economics in the theory of property rights. Due to the importance of residential property for the functioning of households, literature emphasizes a social character of housing and an important role of public sector in providing citizens with decent housing conditions. Discussion about the role of private and public sectors in housing market is still open. The main aim of the article is to present changes in the functioning of housing markets and evolution of housing policy in the context of the theory of property rights.